A contrast of lead immobilization via bioapatite under elevated CO2 between acidic and alkaline soils. (9th October 2018) - Tian, D.; Lai, Z.; Zou, X.; Guo, C.; Tang, L.; Su, M.; Li, Z.; Hu, S.
Abstract: The feasibility of Pb immobilization via bioapatite (BAp) and CO2 in the acidic red soil (RS) and saline‐alkaline soil (SS) was compared in this study. The elevated CO2 (10% in air) significantly promoted the dissolution of BAp in water, that is, the concentrations of released P were enhanced from 2 to 20 ppm as pH decreased from 6.9 to 5.6. Then, it was shown that 30–40% TCLP leached Pb was removed from RS and SS, with the combination of BAp addition and CO2 elevation. In RS, the addition of BAp (even without CO2 ) could significantly increase water‐soluble P. Moreover, some Pb cations were adsorbed onto iron (hydr)oxides within RS. In contrast, CO2 elevation is essential for enhancing P release in SS as it dramatically increased the dissolution of phosphates. The released P then reacted with Pb cations to form insoluble pyromorphite. Therefore, this combination is effective for Pb immobilization in saline‐alkaline soil whereas adding solely BAp is feasible for acid soil.